Steal and theft: nomination strategy in the celtic area - Tatyana Mikhailova (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2023)
The work concerns itself with studying the way the notions thief and theft, which the author considers to be rather late and secondary, are realized in Celtic languages in diachronic perspective. The author constructs the original four-component model of the contemporary notion theft, and traces, on the basis of comparative material, the development of the original notions the model is based on (a secret action, deprivation through the distancing stage, doing harm, agence’s personal interest). Those notions prove to be basic for the emergence and development of corresponding terms during linguistic and social evolution. The verbal use of the tablets against thieves from Roman Bath is analyzed and a new interpretation of the French voler fly - voler steal is geven. The work also suggests the novel etymology for the main verb for stealing in Modern Irish – goid, based on early uses of the verb meaning “distancing” and later – “deprivation”. Examples from the Life of Saint Brigit gives the possibility to see the difference of contextual use and meaning changes of the term used by the same author. At the same time late poetry could give examples of the use of Nomen agentis in the meaning not "thief' but depriver. gaduidhe na geamhoidhche - (17 c.) is not a person who stels something but rather a man who deprives a winter night from its coldness and darkness. The author suppose, it is not a metaphor but an old meaning of the stem. The new etymology of Irish verb to steal is supported by comparison with Old Greek verb and also Chek verb otchugdit in the meaning the steal, jus from the supposed lexeme - thujoj (an early borrowing in Slavonic from a Germanic language). At the same time, the semantic shift could be universal.